2012
DOI: 10.1017/s0033291712002383
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal dysfunction during emotion regulation in generalized anxiety and panic disorders

Abstract: Background The mechanisms that contribute to emotion dysregulation in anxiety disorders are not well understood. Two common disorders, Generalized Anxiety Disorder (GAD) and Panic Disorder (PD), were examined to test the hypothesis that both disorders are characterized by hypo-activation in prefrontal cortex (PFC) during emotion regulation. A competing hypothesis that GAD in particular is characterized by PFC hyper-activation during emotion regulation (reflecting overactive top-down control) also was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
162
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 46 publications
13
162
2
1
Order By: Relevance
“…These findings are compatible with what Ball et al (Ball et al, 2013) have suggested about GAD dysfunction in emotional regulation process: the inability to sufficiently engage PFC in the service of emotion regulation could be a consequence of a chronic over-responsiveness of limbic circuitry that would, in turn, fatigue the topdown system, rendering it unable to effectively exert control when needed (Ball et al, 2013). Thus, the more chronic and severe the pathology, the less the PFC would be activated.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These findings are compatible with what Ball et al (Ball et al, 2013) have suggested about GAD dysfunction in emotional regulation process: the inability to sufficiently engage PFC in the service of emotion regulation could be a consequence of a chronic over-responsiveness of limbic circuitry that would, in turn, fatigue the topdown system, rendering it unable to effectively exert control when needed (Ball et al, 2013). Thus, the more chronic and severe the pathology, the less the PFC would be activated.…”
Section: Discussionsupporting
confidence: 87%
“…For the Reappraise condition, participants were asked to 'change the way that you think about the picture in order to decrease your negative emotions'. Suggested reappraisal strategies included generating a positive interpretation or taking a more detached perspective (Ball et al, 2013). As results, patients with GAD and PD demonstrated less dorsolateral and dorsomedial PFC activation than healthy controls during cognitive modulation of emotion (for both maintenance and reappraisal processes) and those with the least PFC activation reported the greatest anxiety severity and impairment.…”
Section: ) Studies Analyzing the "Emotional Dysregulation Model"mentioning
confidence: 76%
See 1 more Smart Citation
“…During reappraisal of negative stimuli, increased activity in the VLPFC, DLPFC, and mPFC regions is associated with diminished amygdala reactivity to negative stimuli as well as decreased perceived negative affect (21). Amygdala and PFC dysregulation has also been observed in populations with mood dysregulation, including depression (22), anxiety disorders (23,24) including posttraumatic stress disorder (25), impulsive aggression (26), and substance abuse (27). Aberrant amygdala reactivity and inefficient or blunted PFC regulatory function are considered a neurobiological mechanism involved in impaired emotion regulation in these psychiatric disorders.…”
mentioning
confidence: 99%
“…Multi-modal neuroimaging studies provide considerable support for abnormalities in the structure, function, and functional connectivity of the PFC and amygdala in these disorders [5][6][7][8][9] . In addition, recent studies have also implicated abnormalities in the white matter connections between the PFC and amygdala in anxiety and depression, particularly in the ventral prefrontal white matter [10,11] .…”
mentioning
confidence: 99%